The Unity of Veblen's Theoretical System - Anderson, Karl L. (Quarterly Journal of Economics, 1933)
I. Introductory; neglect of Veblen's general theory, 598.— II. His main criticisms of economics, and the fundamental standpoint implied therein, 600.— III. Psychological postulates of Veblen's theory; the evolutionary idea, 602.— IV. Summary of the theory: the savage era, 605; the barbarian era, 607; the period of handicraft, 611; the age of the machine process, 613.— V. Analysis of the modern economy, 614; its place in the general theory, 617.— VI. Integration of Veblen's ideas, 618; this a system of theory different from the Marshallian, 620.— VII. Criticism of Veblenian psychology, 622; treatment of history, 623; and institutions, 624.— Conclusion; issue of the institutional controversy, 624.